COVID-19 pandemic: euphemism and dysphemism in Jordanian Arabic - Olimat, Sameer Naser (Penerbit Universiti Kebangsaan Malaysia, 2020)
COVID-19 is the major health crisis worldwide nowadays. Linguistic aspects of individuals and communities, including euphemism and dysphemism, were affected by this global challenge because choosing appropriate words to express what speakers intend to say and to reflect what they value or disvalue is a basic part of communication. Euphemism is an acceptable expression used instead of an offensive one to avoid unpleasant connotations, while dysphemism is a derogatory expression with negative suggestions used instead of neutral or polite one to attack something or someone. This paper investigates the use of euphemism and dysphemism in the Jordanian society for dealing with COVID-19. The research was approached from a sociolinguistic perspective and framed mainly within the Theory of Euphemism and Dysphemism by Allan and Burridge (1991; 2006) together with Warren’s model of euphemism (1992) and Lakoff and Johnson’s Conceptual Metaphor Theory (1980). A sample of 200 Jordanians was asked to respond to a questionnaire including demographic information and closed-ended and open-ended questions. The results show that the Jordanians used different euphemistic techniques in daily COVID-19 conversations, namely, metaphor, shift from Arabic into English, medical terms, and abbreviation. They show that the participants hardly adopted dysphemisms when talking about COVID-19. This paper contributes to the limited investigation of ‘pandemic discourse’, and to the understanding of euphemistic and dysphemistic tendencies of Jordanians during global crises. Researchers are recommended to explore paralinguistic features of speakers, namely, hand gestures, facial expressions, eye movements, body language, and tone and pitch of voice, while discussing COVID-19 themes.